Expertise in rural development: A conceptual and empirical analysis. (April 2019) - Lowe, Philip; Phillipson, Jeremy; Proctor, Amy; Gkartzios, Menelaos
Highlights: Expertise presents an encompassing frame to progress the democratisation of knowledge. Neo-endogenous (networked) models of development build on expertise in place or vernacular expertise. Vernacular expertise combines field/place generated and field/place focused knowledge. Vernacular expertise is place-based and hybrid, nourished by outside sources and agents. Development approaches should identify ways to draw upon and strengthen the vernacular expertise of all development agents. Abstract: Understandings of socially distributed expertise as being key to living, interpreting and intervening in the world, are increasingly used in development narratives, referring usually to knowledge sharing across multi-stakeholder partnerships. This movement towards the democratisation of expertise challenges the ideological claim of science to be the exclusive source of objective information, evidence and discovery on which informed decisions and technological developments should be based. But if we reject that claim, what are the implications for the way stakeholders learn, organise and transmit knowledge and skills, and resolve problems? And how do science and expertise come together in development narratives and practices? We address these questions through an examination of the changing relationship between scientific, professional and non-professional expertise in rural development. Firstly, we examine the evolution of models of rural development and knowledge generation over past decades and introduce the concept of vernacular expertise – the expertise that people have and develop that is place-based but crucially nourished by outside sources and agents and which underpins neo-endogenous development models. Secondly, by drawing empirically on qualitative research with rural advisory professionals who support farmer decision making we unpack the composition of vernacular expertise as a fusion of field/place generated and field/place focused knowledge, and consider how it may be better recognised and enhanced in development processes and policy agendas.